Quercetin Alleviates the Accumulation of Superoxide in Sodium Iodate-Induced Retinal Autophagy by Regulating Mitochondrial Reactive Oxygen Species Homeostasis through Enhanced Deacetyl-SOD2 via the Nrf2-PGC-1α-Sirt1 Pathway - Hsu, Min-Yen; Hsiao, Yai-Ping; Lin, Yu-Ta; Chen, Connie; Lee, Chee-Ming; Liao, Wen-Chieh; Tsou, Shang-Chun; Lin, Hui-Wen; Chang, Yuan-Yen (Antioxidants, 2021)
Oxidative damage of retinal pigment epithelium (RPE) cells plays an important role in the pathogenesis of blindness-related diseases, such as age-related macular degeneration (AMD). Quercetin, a bioactive flavonoid compound, has been shown to have a protective effect against oxidative stress-induced cell apoptosis and inflammation in RPE cells; however, the detailed mechanism underlying this protective effect is unclear. Therefore, the aim of this study was to investigate the regulatory mechanism of quercetin in a sodium iodate (NaIO3)-induced retinal damage. The clinical features of the mice, the production of oxidative stress, and the activity of autophagy and mitochondrial biogenesis were examined. In the mouse model, NaIO3 treatment caused changes in the retinal structure and reduced pupil constriction, and quercetin treatment reversed the oxidative stress-related pathology by decreasing the level of superoxide dismutase 2 (SOD2) while enhancing the serum levels of catalase and glutathione. The increased level of reactive oxygen species in the NaIO3-treated ARPE19 cells was improved by treatment with quercetin, accompanied by a reduction in autophagy and mitochondrial biogenesis. Our findings indicated that the effects of quercetin on regulating the generation of mtROS were dependent on increased levels of deacetyl-SOD2 through the Nrf2-PGC-1α-Sirt1 signaling pathway. These results demonstrated that quercetin may have potential therapeutic efficacy for the treatment of AMD through the regulation of mtROS homeostasis.